Neighbors, Drought, and Nitrogen Application Affect the Root Morphological Plasticity of Dalbergia odorifera - Xiang, Li-Shan; Miao, Ling-Feng; Yang, Fan (Frontiers in Plant Science, 2021)
In forest dynamics, neighbor-induced root morphological plasticity (RMP) is species specific and environment dependent. However, related studies on leguminous woody trees remain obscure. The objectives of this study were to evaluate root morphological response of the leguminous woody Dalbergia odorifera T. Chen to different N-fixing niche neighbors under root system contact and isolated models and to evaluate whether such response can be modified by drought and nitrogen application. Meanwhile, the relationship between root morphology and relative competitiveness of the whole D. odorifera seedling was also assessed. D. odorifera seedlings from woody Leguminosae Family were used as target species and grown with the following: the same N-fixing niche D. odorifera; heterogenous but con-Leguminous Family Delonix regia; and non-Leguminous Family Swietenia mahagoni. All plants were grown under two watering conditions (100% and 30% field capacities) and two levels of nitrogen conditions (non-application and application). Meanwhile, two planting models (root system contact in experiment 1; root system isolation in experiment 2) were applied between neighboring seedlings. RMP of D. odorifera was assessed on the basis of root morphology, root system classification, root nodules, and RMP-related indexes. The growth of D. odorifera was estimated on the basis of the relative growth ratio and leaf N content. The relative competitiveness of the whole D. odorifera seedling was evaluated through relative yield. Experiment 1 result showed that D. odorifera used different RMP responses to a different N-fixing niche neighbor with root system contact. The RMP of D. odorifera was promoted by the different N-fixing niche neighbor under the conditions of drought or N deficiency. Drought improved the RMP of D. odorifera exposed to a different N-fixing niche neighbor. N application converted the promoting effect of D. regia into inhibitory effect on RMP under well-watered conditions. Experiment 2 result showed that the belowground interaction with a different N-fixing niche neighbor may be the only way to influence RMP due to the negligible aboveground interaction. Finally, correlation analysis showed that the RMP induced by neighbors might predict the relative competitiveness of the whole D. odorifera seedling under the conditions of drought or N deficiency.